Analog-to-digital conversion - Pelgrom, Marcel J. M. (Springer, 2013)
"This textbook is appropriate for use in graduate-level curricula in analog to digital conversion, as well as for practicing engineers in need of a state-of-the-art reference on data converters. It discusses various analog-to-digital conversion principles, including sampling, quantization, reference generation, nyquist architectures and sigma-delta modulation. This book presents an overview of the state-of-the-art in this field and focuses on issues of optimizing accuracy and speed, while reducing the power level. This new, second edition emphasizes novel calibration concepts, the specific requirements of new systems, the consequences of 22-nm technology and the need for a more statistical approach to accuracy. Pedagogical enhancements to this edition include more than twice the exercises available in the first edition, solved examples to introduce all key, new concepts and warnings, remarks and hints, from a practitioner's perspective, wherever appropriate. Considerable background information and practical tips, from designing a PCB, to lay-out aspects, to trade-offs on system level, complement the discussion of basic principles, making this book a valuable reference for the experienced engineer"--